Dynamic key revocation and hybrid cryptographic approaches for secure authentication in the social internet of vehicles - Jawad, Muhammad N.; Al-Shareeda, Mahmood A.; Mustafa, Omar Yawez Mustafa; Almaiah, Mohammed Amin; Shehab, Rami (International Journal of Innovative Research and Scientific Studies, 2025)
Analysis of repeated attack signatures is important because of the rapid evolution of the Social Internet of Vehicles (SIoV). However, threats such as replay attacks, session hijacking, and key reuse make secure communication between vehicles, roadside units (RSUs), and the fog node difficult. Traditional models for authentication are limited by computational overhead and lack quick key revocation. In response to these challenges, we propose a hybrid cryptographic authentication scheme that combines a Zero-Knowledge Proof (ZKP) with AES-GCM encryption. Our protocol implements a dynamic key revocation mechanism to avoid rogue and session key migration, minimizing re-authentication delay. Security analysis in the Real-Oracle Random (ROR) model shows that it is not vulnerable to impersonation or replay attacks. Evaluations demonstrate decreases of 58% in authentication latency while achieving 45% and 72% improvements in communication and computation efficiency, respectively. Our approach is also scalable and secure, providing SIoV with higher reliability for automotive applications in the vehicular networks of the future.